(untitled) (Revista Lusófona de Educação, 2020)
Two fundamental critical thinking skills that students are expected to develop during their formal education are: the use of evidence for justifying their positions, and the consideration of objections or contrary opinions in their own reasoning. These skills, fully manifested in argumentative reasoning, have not been sufficiently addressed in higher education research. This exploratory case study sheds light on a specific type of argumentative reasoning particularly important for graduate students: the argument-based academic writing. A Ph.D. seminar course (22 lecture hours) was developed based on two main concepts of argumentation theory, namely argumentation schemes and the heuristic uses thereof, i.e. paraschemes. The course was delivered to seven first-year Ph.D. students at a public Portuguese University. The students’ reasoning skills were assessed through their written drafts before and after the three-month course. The assessment method used was mixed (qualitative and quantitative). A significant change was observed in the increase of sound argumentation strategies and the decrease of the ungrounded ones in students’ academic writing. The study concludes with recommendations for both the teaching of academic writing at a graduate level and the promotion of critical thinking skills. Keywords: academic writing; argumentation; critical thinking; Phd students